Fire effects on invertebrate fauna of forest and woodland - Majer, Jonathan (1985)
An understanding of the influence of fire on soil and litter invertebrates in Australian ecosystems is important in view of the important role of these animals in nutrient cycling (Hutson 1983), maintenance of soil structure (Greenslade & Greenslade 1983) and provision of food for certain vertebrate animals such as tne mardo (Hindmarsh & Majer 1977).